27-Hydroxycholesterol Contributes to Lysosomal Membrane Permeabilization-Mediated Pyroptosis in Co-cultured SH-SY5Y Cells and C6 Cells - Chen, Si; Zhou, Cui; Yu, Huiyan; Tao, Lingwei; An, Yu; Zhang, Xiaona; Wang, Ying; Wang, Yushan; Xiao, Rong (Frontiers in Molecular Neuroscience, 2019)
Purpose: Emerging evidence suggests that 27-Hydroxycholesterol (27-OHC) causes neurodegenerative diseases through induction of cytotoxicity and cholesterol metabolism disorder. The objective of this study is to determine the impacts of 27-OHC on lysosomal membrane permeabilization (LMP) and pyroptosis in neurons in the development of neural degenerative diseases. Methods: In this study, SH-SY5Y cells and C6 cells were co-cultured in vitro to investigate the influence of 27-OHC on the function of lysosome, lysosomal membrane permeabilization (LMP) and pyroptosis related factors in neuron. Lyso Tracker Red was used to detect the changes of lysosome pH, volume and number. Acridine Orange (AO) Staining was also used to detect the LMP in neurons. Then the morphological changes of cells were observed by scanning electron microscope. The content of lysosome function associated proteins (including Cathepsin B, Cathepsin D, LAMP-1, LAMP-2) and the pyroptosis associated proteins (including NLRP3, GSDMD, caspase-1and IL-1β) were detected through Western blot. Results: Results showed higher levels of lysosome function associated proteins, such as Cathepsin B (p < 0.05), Cathepsin D (p < 0.05), LAMP-1 (p < 0.01), LAMP-2) (p < 0.01) in 27-OHC treated group than that in control group. AO Staining and Lyso-Tracker Red Staining showed that 27-OHC induced lysosome dysfunction with LMP. Content of pyroptosis related factor proteins, such as GSDMD (p < 0.01), NLRP3 (p < 0.001), caspase-1 (p < 0.01) and IL-1β (p < 0.01), were increased in 27-OHC treated neurons. Additionally, cathepsin B was leaked through LMP into the cytosol and induced pyroptosis. Results from the present study also suggested that the CTSB is involved in activation of pyroptosis. Conclusions: Our data indicate that 27-OHC contributes to the pathogenesis of cell death by inducing LMP and pyroptosis in neurons.